Xenophon on the Achaemenid gerrhophoroi, - Podrazik, Michał (Anabasis. Studia Classica et Orientalia, 2020)
The Achaemenid soldiers known under the Greek term γερροφόροι appear in the writing of Xenophon, who witnessed them among the forces of the Achaemenid Great King Artaxerxes II at the Battle of Cunaxa (401 BC). As the meaning of the term indicates, they were soldiers using a γέρρον, which in the context of military arms refers to a wicker-made shield. The aim of the article is to analyze references to the Achaemenid γερροφόροι provided by Xenophon.